Health Risk Assessment of Heavy Metal Accumulation in Rice Grains Cultivated by Industrial Effluents - Sheeza Rafaqat; Ambreen Aslam; Umair Riaz; Ibtisam M. Alsudays; Sabiha Javied; Nayyar Hassan; Muneera A. Saleh; Khalid H. Alamer; Qamar uz Zaman (Applied and Environmental Soil Science)
Pakistan, an agricultural country, is facing a severe water shortage due to crop cultivation. Therefore, industrial wastewater can be efficiently utilized in many regions to irrigate crops as it contains a high concentration of organic and inorganic elements. Heavy metal concentrations have also excessively been found in industrial effluents, such as cadmium, zinc, cobalt, lead, and others. The present study was conducted to study these elements. To fulfill the purpose of the study, a total number of thirty samples were collected. Ten industrial wastewater samples were collected from the Marala–Ravi Link Canal which passes from Village Dheli in the Narowal district used for irrigation. Ten different soil samples were taken from the fields where the rice was grown. Ten samples of three different rice varieties were collected from the fields grown on this canal water. The result indicates that the sample’s soil texture was loam with a pH of less than 8.3. Across all samples, the sequence that follows the pattern is Fe > Mn > Zn > Cu. A variety of rice such as Super rice, Kainat rice, and Laal rice resulted in Zn (less than 7.89 ppm); Cu (less than 7.23 ppm); Fe (less than 7.63 ppm); and Mn (less than 4.55 ppm). It is evident from the findings of the research that Marala–Ravi Link Canal contains certain heavy metals within the permissible limits except for Pb (0.99 ± 0.09 ppm) in Super Kernel rice samples and Cu (7.23 ± 0.09 ppm) in Kainat rice samples. However, only one variety of rice, which is Laal rice, is good for human health. The health risk index at all sites was less than one. Consistent examination is further recommended to limit health hazards instigated using rice polluted with a greater concentration of Cd.